A post hoc comparison of levodopa-carbidopa intestinal gel daytime monotherapy vs polytherapy safety and efficacy in patients with advanced Parkinson's disease: Results from 6 phase 3/3b open-label studies. (2020) - Boyd, James T.; Zadikoff, Cindy; Benesh, Janet A.; Zamudio, Jorge; Robieson, Weining Z.; Kukreja, Pavnit; Yokoyama, Masayuki; Siddiqui, Mustafa S.
Abstract: Introduction: As Parkinson's disease (PD) progresses, the number/frequency of PD medications tend to increase, which is correlated with decreased patient compliance and suboptimal control of PD symptoms. We investigated efficacy and safety of levodopa-carbidopa intestinal gel (LCIG) daytime monotherapy (with or without nighttime oral levodopa-carbidopa) compared with polytherapy (LCIG with ≥1 adjunctive PD therapy) in advanced PD patients. Methods: This post hoc descriptive study compared LCIG stable daytime monotherapy with LCIG stable polytherapy in all six phase 3/3b open-label studies from both US and international sites; because of study design variability, pooling data for comparison was not appropriate. Efficacy assessments included PD diary data (mean change from baseline in "Off" time and "On" time with or without troublesome dyskinesia), mean Unified PD Rating Scale scores (Parts II and III), and 39-item Parkinson's Disease Questionnaire (PDQ-39) summary index. Adverse events were also assessed. Results: Overall, LCIG daytime monotherapy and polytherapy demonstrated similar efficacy/safety profiles in advanced PD patients, regardless of treatment duration or population. LCIG monotherapy vs. polytherapy groups experienced similar mean decreases in "Off" time (4.6 vs. 4.1 h/day) and similar increases in "On" time without troublesome dyskinesia (4.6 vs. 4.1 h/day). In most studies, PDQ-39 summary index scores were reduced from baseline by ≥5 points, regardless of patient population or study duration. Adverse events not related to the procedure/device were similar in both groups. Conclusion: Our data suggest that, for appropriate patients, LCIG monotherapy can provide a more simplified treatment option with similar efficacy and safety. Highlights: Advanced Parkinson's disease (PD) often requires a large number of medications Levodopa-carbidopa intestinal gel (LCIG) is administered continuously LCIG monotherapy vs. polytherapy was assessed in six phase 3/3b studies LCIG monotherapy and polytherapy had similar efficacy and safety profiles LCIG monotherapy may provide a more simplified treatment option for advanced PD